AUDIT ENERGI LISTRIK DAN BOILER PABRIK KELAPA SAWIT KAPASITAS 60 TON/JAM - Muhamad Mustangin; Saptyaji Harnowo (Institut Teknologi Sawit Indonesia (ITSI), 2020)
Palm Oil Factory Energy consists of steam and electricity. To increase the performance, energy will to beaudited. Electrical measurements are carried out at the power house, panels at each station and some electricmotors. Measurement in the main panel uses a power quality analyzer that can measure power, power factor,harmonics, unbalance and other electrical parameters. For measurement of mechanical equipment with steamenergy such as boilers and turbines using temperature measuring devices with infrared thermal imaging toolsFLIR brand. The quality of electric power with a total harmonic of 5.12% and individual harmonics of 2.78%.Voltage and current unbalance are 0.09% and 0.15%. Voltage drop is equal to 3 volts. The use of electricityutilities is 22.81 kW / ton FFB. The factory has cos phi of 0.84 but requires automatic power factor correction.The efficiency of boilers is 64.19% with the biggest losses being dry flue gas of 20.19% and oyher boiler of67.82% with the biggest losses being dry flue gas of 16.45%.